Nulturing Local Culture: Social Education Values in Fida' Activities in Tingkir Tengah Subdistrict, Salatiga City - Khotim Ahsan; Saeed Akhtar; Mohammad Abu Shareea (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The aim of this research is to determine the values of social education with Fida' activities in Tingkir Tengah Subdistrict, Salatiga City. Methodology: This research is qualitative research, namely research that is descriptive, explaining in detail the object being studied. Data research in the form of written or spoken words obtained from people who observed. This research seeks to determine the values of social education in Fida' activities in Tingkir Tengah sub-district. Main Findings: The findings of this research show that the values of social education Contained in Fida' activities include: (1) establishing ukhuwah islamiyah (2) togetherness (3) mutual help. These findings show that in religious activities it is not only about pursuing rewards, however also social interaction with other people, not just concerned with khablumminallah but also khablum minannas Novelty/Originality of this study: The integration of social education values through Fida' activities in Tingkir Tengah Village, Salatiga City is an interesting innovation. By combining educational approaches and social activities, this program not only provides practical knowledge to the community regarding philanthropic and humanitarian activities, but also encourages active participation in building social solidarity in the community. By providing social values as the core of Fida' activities, this initiative does not just disseminate information, but also shapes the character and social awareness of residents, bringing a sustainable positive impact to the development of society in Tingkir Tengah Subdistrict.